ANALISIS YURIDIS MENGENAI KEISTIMEWAAN BAGI PELAKU USAHA KECIL TERKAIT DENGAN PERSAINGAN USAHA TIDAK SEHAT - Manik Sidartha, Ngurah; Markeling, I Ketut (Kertha Semaya : Journal Ilmu Hukum, 2014)
Paper titled “Judicial Analysis Concerning Privileges for the Small Business Actors Related to Unfair Business Competition“, using normative writing method trough statute approach. Issues that raised in this paper is concerning privileges for the small business actors related to unfair business competition. Form of privileges for small business actors related to unfair competition, has been regulated in Act No.5 Year 1999 Concerning Prohibition of Monopolistic Practices and Unfair Business Competition Article 50, the exception for small business actors from the entry into force of the Act No.5 Year 1999. It’s because there is a perception that small business actors still need of protection in order to grow, and also the social reason that the weak position of small business actors that would not have not been assessed monopoly activities.
Keywords: Law protection, Small business actors, Unfair business competition, Exception